LIFESTYLE AND CONSUMER PREFERENCES IN CHOOSING LOCAL OR FOREIGN BRANDS: A STUDY OF CONSUMER BEHAVIOR IN SURAKARTA – INDONESIA - Budhi Haryanto; Awang Febrianto; Edi Cahyono (Management Study Program, Faculty of Business and Economics, Petra Christian University, 2019)
This study discusses the relationship between lifestyle and individual preferences in choosing local or foreign brands. The sample consisted of 250 people, taken randomly through surveys in several public places in Surakarta - Indonesia, including the department stores, traditional markets, or other public areas, where many people were there and were willing to become research participants. Furthermore, the collected data is processed using factor analysis to reduce lifestyle dimensions, and logistic regression analysis is used to explain the relationship between lifestyle dimensions and preferences in choosing a local brand or foreign brand, in this case represented by Wong Solo Grilled Chicken (WSGC) or Kentucky Fried Chicken (KFC).The test results indicate 13 dimensions of lifestyle, and only 5 dimensions are significantly related to brand preference: (1) individuals who have a fashion consciousness lifestyle tend to choose KFC rather than WSGC, (2) individuals with health consciousness lifestyles tend to choose WSGC rather than KFC, (3) individuals with leadership lifestyles tend choosing KFC rather than WSGC, (4) individuals with attentiveness lifestyle tend to choose WSGC rather than KFC, and (5) individuals with extroversion lifestyles tend to choose KFC rather than WSGC. This study also discusses the implications of studies related to the contribution of theory, practitioners, and possibilities for future studies